Implementation of altimeter data assimilation on a regional wave forecasting system and its impact on wave and swell surge forecast in the Indian Ocean. (1st October 2021) - Seemanth, M.; Remya, P.G.; Bhowmick, Suchandra Aich; Sharma, Rashmi; Balakrishnan Nair, T.M.; Kumar, Raj; Chakraborty, Arun
Abstract: In the present work, we have operationally implemented a data assimilation (DA) scheme in the wave forecasting system at the Indian operational agency, Indian National Centre for Ocean Information Services (INCOIS). Significant Wave Height (SWH) measurements from the SARAL/AltiKa, Jason-2 and Jason-3 altimeters were assimilated using the Optimal Interpolation technique. The impact of altimeter DA towards improving the reliability of wave predictions in the Indian Ocean is evaluated by validating the forecasted wave parameters with buoy observations. The assimilation of altimeter data showed considerable improvement in the wave predictions. SWH forecast in the northern Indian Ocean region improved up to ~15 % in the first 24 h period. The improvement in forecasted wave parameters were due to the correction in swell forecast, which persists throughout the forecast period. For wind-sea forecast, impact of DA was less visible (~4–6% improvement up to forecast lead time of 24 h), as it is primarily driven by local wind fields. The positive impact of DA on the swell forecast is further established considering a swell surge event, named Kallakkadal . Highlights: Implemented a data assimilation scheme on the wave forecasting system at INCOIS. Assimilation of altimeter measured SWH improved the wave predictions. Significant improvement in swell forecast is achieved.